ANALISIS PENGARUH FAKTOR KEMISKINAN TERHADAP TINGKAT KESEHATAN DAN GAYA HIDUP MASYARAKAT DESA SURALAGA, LOMBOK TIMUR, MENGGUNAKAN ALGORITMA SUPPORT VECTOR MACHINE (SVM) - Muhammad Wasil; Mahpuz Mahpuz (Fakultas Teknik Universitas Hamzanwadi, 2021)
The level of poverty in Indonesia is currently an important task for the government, both in cities and in villages. As time goes by and the nation's economy is arguably unstable, the poverty level of the community cannot be controlled properly. Especially for rural areas or remote and remote villages, such as in the province of NTB, East Lombok Regency, especially in Suralaga Village. The people in Suralaga Village, who generally only have income from farming and raising livestock, are unable to meet their daily needs, which are increasingly soaring. Not only to meet economic needs, they may find it difficult to fulfill their educational needs. The results of farming or raising them, which has a grace period from planting to harvest, require a lot of money. Therefore, the income they have is not stable. This instability causes the economy of the community in the village to be classified as middle to lower class. To find out the extent of the influence of the poverty factor on the level of health, an analysis of the influence of the poverty factor on the health level and lifestyle of the people of Suralaga Village, East Lombok was carried out using the Support Vector Machine (SVM) algorithm. The experimental results shown, have concluded that data processing to determine the purpose of this study, using the Support Vector Machine algorithm, poverty to the health level of the Suralaga Village community is very large and provides an illustration that the average Suralaga Village community is included in the category of people who do not pay attention to the elements. health with an accuracy rate of 73.77%, when viewed based on the distribution of data used